Être formé et former à la médiation paysagère : place dans les cursus de paysagistes et regards croisés d’enseignants et d’apprenants - Sophie Bonin; Claire Fonticelli; Anne Sgard; Monique Toublanc (Projets de Paysage)
This article presents the results of a survey on landscape mediation training in seven institutions in France and Switzerland. Mediation, and even participation, have become issues in the training of landscape architects because of the expectations from institutions due namely to the European Landscape Convention, but also because of the need for future landscape architects to gain a greater knowledge of local actors. The objective of the survey, carried out by four researchers from the "Didactique du paysage" team, is to find out whether mediation is taught, and if so, how and to which ends. The article starts by describing the expectations of a group of students and how they experienced an exercise in mediation. Mediation, discreet yet present in curricula, is then analysed based on an examination of fundamental texts in the teaching of landscape architecture in France and of pedagogical references. Finally, based on interviews with a panel of teachers, teaching practices and references are analysed to establish whether a common didactic approach can be identified.